COMPARATIVE STUDY OF REGIONAL ELECTION FROM FIVE PERSPECTIVES: A RESPONSE TO THE PROPOSAL OF THE 8TH PRESIDENT OF INDONESIA - Wawan Gunawan; Yaya Mulyana A Aziz (LPSDI Bina Patria, 2025)
This research is a response to the statement made by President Prabowo Subianto regarding the large budget required for the implementation of the 2024 simultaneous regional elections. Using a literature review approach, the author conducts a comparative study of regional elections from five perspectives: democracy, constitution, budget, corrupt behavior, and national security. The findings indicate that from the democracy aspect, regional elections, whether directly or through the DPRD, can be considered democratic as long as the process runs democratically. The constitutional aspect shows that law. of the UUD 1945 should not only be interpreted as a direct regional election but can also be understood as a regional election through the DPRD. From the budget perspective, regional elections require significant funding, which must be borne by the state and the candidates themselves. This situation triggers corrupt behavior among the elected candidates in direct regional elections. Lastly, the direct election of regional heads also has the potential to disrupt security stability, as it often leads to conflicts due to differing political choices